2005
DOI: 10.1002/jts.20032
|View full text |Cite
|
Sign up to set email alerts
|

Personal resources, coping self‐efficacy, and quake exposure as predictors of psychological distress following the 1999 earthquake in Turkey

Abstract: This study examined the predictive power of personal resources (i.e., self-esteem, optimism, and perceived control), severity of earthquake experience (i.e., material and human loss and perceived threat), and coping self-efficacy (CSE) on general distress, intrusion, and avoidance symptoms among the survivors of the 1999 Marmara earthquake in Turkey. Specifically, we expected that CSE would mediate the links between personal resources, severity of earthquake experience, and distress. Survivors (N = 336) filled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
119
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(136 citation statements)
references
References 36 publications
(59 reference statements)
14
119
0
3
Order By: Relevance
“…Not all individuals that experience a traumatic event develop PTSD, and the importance of perceived behavioral control in determining resilience has been often noted (Charney, 2004). As specific examples, a careful analysis revealed that a high level of perceived control blunted the impact of the 1999 Marmara earthquake in Turkey (Sumer et al, 2005) and perceived control during a myocardial infarction (MI) reduced the likelihood of PTSD following the MI (Doerfler et al, 2005). Many other examples could be cited (e.g., Palyo and Beck, (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Not all individuals that experience a traumatic event develop PTSD, and the importance of perceived behavioral control in determining resilience has been often noted (Charney, 2004). As specific examples, a careful analysis revealed that a high level of perceived control blunted the impact of the 1999 Marmara earthquake in Turkey (Sumer et al, 2005) and perceived control during a myocardial infarction (MI) reduced the likelihood of PTSD following the MI (Doerfler et al, 2005). Many other examples could be cited (e.g., Palyo and Beck, (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Optimism can also positively influence disaster victims' mental well-being through enhancing their CSE [7,12,13]. In fact, certain personality traits and mood states, such as optimism, have also been positively associated with PTG [29].…”
Section: Discussionmentioning
confidence: 99%
“…Findings gathered from earthquake, flood, and hurricane survivors demonstrate a dose-response relationship between CSE and both short-and long-term global distress. Personal attributes, such as optimism and self-esteem, significantly advanced CSE's positive impact on distress triggered by natural disasters [11][12][13]. Recent research also seems to suggest that individuals' disaster experiences may, in some instances, lead to post-traumatic growth (PTG), the strength gained to overcome stress and improve quality of life [14,15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…30 The limited disaster literature on efficacy perceptions has focused on self-efficacy as a determinant of mental and behavioral health 31 and posttraumatic recovery after a disaster. [32][33][34] Similar research has identified correlations between optimism and superior performance in adverse situations. 35 In this article, disaster recovery is defined in accordance with the Federal Emergency Management Agency's Framework as follows: "[R]ecovery encompasses more than the restoration of a community's physical structures to its pre-disaster conditions.…”
Section: Lpha Workers and Disaster Recovery: Efficacy-oriented Researmentioning
confidence: 99%